2021
DOI: 10.1002/app.50680
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of anti‐migration transition layer and its application in cast‐in‐case solid rocket motors

Abstract: The polyester‐based transition layers were first synthesized with poly (diethylene glycol adipate), glycerin, and toluene diisocyanate. Then they were coated between the propellant and the liner to improve the bonding performance of the charge and inhibit the migration of the energetic plasticizer in the propellant. The effects of R value (the ratio of the quantity of isocyanate functions NCO with respect to the quantity of hydroxyl functions OH) on migration resistance and bonding performance were also studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…We have confirmed that the interaction between NENA and the polar sites of the polyester matrix is a stronger migration driving force than the concentration gradient. 20 Therefore, for the NENA migration results of the 62, 64, and 66 "homologous" polyester transition layers, our expectation is that as the content of polar groups increases, the amount of NENA migrating into the corresponding layers will gradually increase. However, the experimental result is completely in contrast to expectations.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We have confirmed that the interaction between NENA and the polar sites of the polyester matrix is a stronger migration driving force than the concentration gradient. 20 Therefore, for the NENA migration results of the 62, 64, and 66 "homologous" polyester transition layers, our expectation is that as the content of polar groups increases, the amount of NENA migrating into the corresponding layers will gradually increase. However, the experimental result is completely in contrast to expectations.…”
Section: Resultsmentioning
confidence: 95%
“…The molar ratio of -NCO/-OH of the reactants in all transition layer formulations was 1.5 (in the polyurethane industry, the ratio is usually named R value, that is, R = 1.5) and the molar ratio of toluene diisocyanate/glycerin = 3, which is the optimized result of our previous work . When preparing the transition layer film, first, stoichiometric amounts of the polyester binder and glycerin (AR, Sarn Chemical Technology Co., Ltd.) were added to the beaker, and stirred well at 60 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, the improvement of anti-migration properties is urgently needed. Numerous efforts have been put into hindering the migration of plasticizers [ 10 , 11 , 12 ]. Some scholars [ 10 ] tried to reduce the diffusion coefficient by adding a barrier layer.…”
Section: Introductionmentioning
confidence: 99%
“…In order to avoid interfacial debonding, the liner is required to have certain mechanical properties, such as tensile properties and bonding properties. Zhang et al [ 28 ] used poly (adipic diethylene glycol), glycerol and toluene diisocyanate to synthesize a polyester-based transition layer, which was applied between the propellant and the liner layer. This substantially improved the bonding properties between the interfaces and effectively inhibited the migration of high-energy plasticizers.…”
Section: Introductionmentioning
confidence: 99%